Estimating the costs of Israel’s four COVID-19 waves - Panagiotis TSIGARIS; Jaime A. TEIXEIRA DA SILVA; Francesco CHIRICO (Journal of Health and Social Sciences)
Introduction: This paper focuses on the health and economic costs of the COVID-19 pandemic to Israel during the first four waves (2020-2021) of the pandemic. Methods: Four costs of the pandemic in Israel were assessed: economic losses, costs of premature mortality, mental health, and health impairment, estimated using IMF forecasts of GDP with COVID- 19 relative to GDP without COVID-19 (i.e., the counterfactual) from 2019 until 2030, estimated number of deaths based on IHME data multiplied by VSL values, a Cutler and Summers method that assessed disutility using HRQoL, and the loss in VSL due to the disutility from suffering, respectively. Results: The four primary waves of COVID-19 cases and deaths in Israel occurred between early 2020 and October 2021. After the first three waves between April and June 2021, excessive relaxation of stringency measures allowed the highly infectious delta variant (B.1.617.2) to spread, aided by an inability to vaccinate a high percentage of the population (never exceeding ~63%), leading to a fourth wave. Costs of the pandemic are estimated (in billions of 2017 constant Int$) at Int$81.7 for mental health, at Int$80.3 for economic losses, Int$53.3 for the cost of premature mortality, and Int$39.4 billion for health impairment. The total cost of the pandemic is estimated at Int$254.7 billion or 70% of the 2019 GDP of Israel but could be as high as Int$667 billion. Discussion: Stringency policies to contain the virus' spread in Israel have been pro-cyclical, i.e., as infection rate increased so did stringency policies, and vice versa. Our study offers policymakers important suggestions regarding cost-effectiveness analysis for this and future pandemics. Balancing economic and health priorities is needed.